2006
DOI: 10.1007/s10661-006-7051-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Air Quality After the Implementation of Compressed Natural Gas (CNG) as Fuel in Public Transport in Delhi, India

Abstract: Public transport in Delhi was amended by the Supreme Court of India to use Compressed Natural Gas (CNG) instead of diesel or petrol. After the implementation of CNG since April 2001, Delhi has the highest fraction of CNG-run public vehicles in the world and most of them were introduced within 20 months. In the present study, the concentrations of various criteria air pollutants (SPM, PM(10), CO, SO(2) and NO(x)) and organic pollutants such as benzene, toluene, xylene (BTX) and polycyclic aromatic hydrocarbons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(59 citation statements)
references
References 14 publications
5
53
1
Order By: Relevance
“…Dondero and Goldemberg (2005) compared the emissions of converted CNG vehicles with when they ran on gasoline and found them to exhibit average reductions of 53%, 55%, and 20% in CO, NMHCs, and CO 2 emissions, respectively, but average increases of 162% and 171% in HC and NO x emissions, respectively. Several studies examined the impacts of air quality after the introduction of CNG found mixed results (Chelani and Devotta, 2007;Goyal and Sidhartha, 2003;Kathuria, 2004;Ravindra et al, 2006). Goyal and Sidhartha (2003) compared the air quality in Delhi during the years 1995-2000 (without CNG) with the year 2001 (with CNG) and found decreases in ambient air concentration of CO, sulphur dioxide (SO 2 ), suspended particulate matter (SPM), and NO x emitted from the transport sector.…”
Section: Discussionmentioning
confidence: 99%
“…Dondero and Goldemberg (2005) compared the emissions of converted CNG vehicles with when they ran on gasoline and found them to exhibit average reductions of 53%, 55%, and 20% in CO, NMHCs, and CO 2 emissions, respectively, but average increases of 162% and 171% in HC and NO x emissions, respectively. Several studies examined the impacts of air quality after the introduction of CNG found mixed results (Chelani and Devotta, 2007;Goyal and Sidhartha, 2003;Kathuria, 2004;Ravindra et al, 2006). Goyal and Sidhartha (2003) compared the air quality in Delhi during the years 1995-2000 (without CNG) with the year 2001 (with CNG) and found decreases in ambient air concentration of CO, sulphur dioxide (SO 2 ), suspended particulate matter (SPM), and NO x emitted from the transport sector.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in order to facilitate the domestic usage (cooking and heating) of natural gas, commercial sales of natural gas for vehicles was banned for the period of December 2013 to February 2014. Various studies have reported the decrease in NO 2 emissions due to increased usage of CNG in vehicles (Ravindra et al, 2005;Goyal et al, 2006;Suthawaree et al, 2012;Agarwal, 2015). Similarly, an interesting feature was observed during the comparison of field campaigns conducted in twins' cities during two different scenarios: i) on 16 November 2012 when CNG was available and ii) on 13 December 2013 when CNG was not available for vehicles.…”
Section: Field Campaign On 13 December 2013mentioning
confidence: 58%
“…Despite remediation actions including implementation of the world's largest compressed natural gas (CNG)-fueled public transportation system, air pollution remains a critical issue (Goyal and Sidhartha, 2003;Ravindra et al, 2006;Chelani and Devotta, 2007;Khillare et al, 2008;Saxena and Ghosh, 2010) The vehicle fleet consists of 63.6% two-wheelers and 30.7% gasoline-fueled passenger vehicles, as well as minor amounts of light commercial vehicles (1.6%), three-wheelers (1.4%), trucks (1.1%), buses (0.8%), and diesel-fueled vehicles (0.5%) (NEERI, 2010). Energy demand increased from ~3100 megawatts (MW) in 2007 to ~5900 MW in 2012 (National Capital Region [NCR] Planning Board.…”
Section: Study Areamentioning
confidence: 99%